Mengkaji Neoliberal Institusionalisme Uni Eropa dalam Problematika Implementasi Kebijakan Migrasi Pada Traktat Lisbon [Assessing the Neoliberal Institutionalism of the European Union through the Problematic Implementation of the Libson Treaty Migration Policy] - - Yusran; Afri Asnelly; - Elistania (Universitas Pelita Harapan, 2016)
As a neoliberal institution, European Union has succeded in integrating. However, after the treaty establishing a constitution for Europe was failed to be ratified, European Union is experiencing setback of legitimacy. European Union later imposed Lisbon Treaty that was arranged right after the failure of constitution treaty. Still, the implementation of Lisbon Treaty triggered some new issues due to its content that is more or less similar to the previous unratified treaty. One of the issues came from the migration policy. The rejection from some of the member countries explained the legitimacy crisis on the institution of European Union. This legitimacy crisis is surely a negative precedent for European Union as a neoliberal institution. As in neoliberal institutionalism, an institution is supposed to be an independent variable when a state decides to cooperate and integrate itself in an institution. This writing is aimed to review the neoliberal institutionalism of European Union in the problems of the migration policy implementation upon Lisbon Treaty.This research used qualitative method, with neoliberal institutionalism as its core theory. This research found that European Union as an institution lacks of consideration towards the condition of its member states in making regulations. This can be seen on how the migration regulation on Lisbon Treaty still could not be implemented uniformly on all the member states. Besides, the refusal of Estonia, Hungary and Slovakia upon this migration regulation strengthen the crisis of legitimacy in European Union as a neoliberal institutionalism.. The spesific finding upon this migration issues on Lisbon Treaty brought us to a conclusion that the neoliberal institutionalism in European Union needs to be examined due to the decadence of the institution’s legitimacy.